Effects of postdeposition heat treatment on the structural and magnetic properties of CoFe2O4 nanoparticles produced by pulsed laser deposition - Fabris, Fernando (2017)
In this work, we investigated the effects of postdeposition heat treatment on structural and magnetic properties of CoFe2O4 nanoparticles produced by pulsed laser deposition. Structural analysis by X-ray diffraction, transmission electron microscopy (TEM) and Mössbauer spectroscopy indicate the formation of a single phase cobalt ferrite nanoparticles with the size ranging from 4.3 to 33.3 nm depending on the annealing temperature. The magnetic properties of the samples were investigated in a wide temperature range (50-400 K). Noticeable effects of the cubic magnetocrystalline anisotropy on the magnetization process of nanoparticles were observed for samples annealed at 450 °C and 600 °C, while for samples as-deposited and annealed at 300 °C the magnetization properties were dominated by a uniaxial effective anisotropy. ΔM technique was used to investigate the magnetic interaction among the nanoparticles. Only demagnetizing interactions were observed for the sample annealed up to 300 °C, while for the samples treated at 450 °C and 600 °C, both magnetizing and demagnetizing interactions were observed. The results are discussed considering the evolution of the nanoparticles' nanostructure with anneals and its effects on the magnetic properties.